The SST alliance: Public theology, scientific reasoning, and skeptical inquiry in a post-truth age - Ted Peters (KAMASEAN: Jurnal Teologi Kristen, 2026)
This article argues that the Christian public theologian engages the wider culture in rational discourse regarding truth versus falsity, information versus disinformation, and the common good over division. In the global struggle to base public policy on accuracy, the public theologian could make a positive contribution by partaking in an alliance made up of Science, Skepticism, and Theology (SST). This SST Alliance should lift up a shared vision of the common good. Through discourse clarification and worldview construction, the theologian should critique both ideological scientism and materialist skepticism for going too far. What is most valuable to the wider culture is the methodological commitment of both science and skepticism to evidence-based reasoning, something the public theologian endorses. Ultimately, by advocating for this interdisciplinary collaboration, this study demonstrates that theology serves as a vital, rational partner in the urgent global quest to combat the proliferation of misinformation and restore the integrity of objective truth in the public square.